Dynamic multimedia content allocation for scarce resource networks. (14th July 2009) - Pande, Amit; Verma, Amit; Mittal, Ankush; Agrawal, Ashish
A serious bottleneck in multimedia e-learning is the non-availability of required bandwidth. While much research has been done on multimedia compression and network resource optimisation, multimedia delivery is still a big concern, especially for scarce resource networks. In this paper we incorporate network-information to determine how various parts of the video frames are encoded. An estimate of the available network bandwidth allows optimal resource sharing between the different frame constituents based on their relative importance and motion. While this scheme is operational for all low motion videos with identifiable Visual Objects (VO), we demonstrate the approach using educational videos.